The Narrative Techniques in Matthias Bel´s Knowledge of the Tekov County - Jozef Kordoš (Slovenska Literatura, 2021)
The goal of the paper is to characterize the narrative techniques that Matthias Bel (1684 – 1749) used in his paper Vedomosti o Tekovskej stolici (Knowledge of the Tekov County, 1742), usually considered to be a historiographic work. It tracks the passages where Bel´s commentary overlaps with other genres or scientific branches, and draws attention to the elements that make it possible to classify the work as a chorography. Bel´s aim was not only to systematically collect the accurate facts about the region but, apparently, also to saturate various needs of well-educated readership that finds pleasure in examining the picture of the region through a miscellaneous collection of natural particularities and specific cultural manifestations. Since the commentary on the Tekov county seeks support in quotations from the travelogue Letters from Travels (1700) written by the Dutch traveller Jakob Tollius (1633 – 1696), the reader explores the region as a traveller not only being accompanied by well-educated and sophisticated Bel, but also regularly through Tollius´s gripping narrations. Another dominant element of the commentary is a number of etiologic legends, which Bel in the position of a collector of oral folk culture presents as an outstanding narrator. Comparison with other authors who also visited and described the region (F. E. Brückmann, E. Brown) shows that these digressions are a specific feature of Bel´s picture of the Tekov county.